ENGLISH LEARNERS’ PERCEPTIONS USING GOOGLE TRANSLATE FOR DOING ASSIGNMENTS: ADVANTAGES AND DISADVANTAGES - Chayyira Channia (Universitas Muhammadiyah Muara Bungo, 2022)
The use of Google translate (GT) for English assignments is now inevitable. Teachers neither can prevent their students to use GT nor can supervise it since all of the learning process has been running online from home to home. Therefore both teachers and students should bring out the advantages of GT to improve English competence and to reduce the disadvantages of using GT. This study is aimed to investigate the learners’ perspectives of using GT for doing English assignments and to describe the advantages and disadvantages of GT. The study is presented in descriptive qualitative design. The data collection instruments are questionnaires and interview. The participants are 198 students of Information system department, University of Putra Indonesia YPTK Padang. The findings of this study showed that for about 80% of English learners depend their English assignments on GT. Based on the learners’ perspective, the advantages of using GT are time saver and instant results and the disadvantages of using GT are inaccuracy in the results relate to cultural context, idiom, sentences with metaphor and pragmatic aspects and laziness for learning the structure of English language. The study also came with the solution to eliminate the disadvantages of using GT.